2019
DOI: 10.4236/jbm.2019.74001
|View full text |Cite
|
Sign up to set email alerts
|

Familial Background as a Hidden Cause for Obesity among College Going Girls

Abstract: Background: Rapid changes in global economies and industrialization have resulted in switch from traditional diets and labor intensive lifestyle to consumption of modern calorie-rich diets loaded with fat and sugar contents, accompanied with sedentary lifestyle further leading to onset of numerous non-communicable, chronic disorders; obesity being one of them. This study aims at investigating risk posed by family history of obesity over the generations for inducing extreme overweight conditions among adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…This is in accordance with the research of Anita et al in 2019 which stated that there exists "familial aggregation" in familial correlations of obese/overweight state during early days of life whereby daughters are more likely to be inflicted upon by parental indices of adiposity than sons. Consistent with these lines, a positive history in family for obesity cases has been highlighted in the present study to be one of the major diagnostic risk factors for the onset of weight gain, equally suggested by many other studies (Mangla et al, 2019). In obese patients, inflammation of adipose tissue occurs and causes insulin resistance and an increase in aromatase expression (in this case the CYP2C19 gene polymorphism) which converts testosterone to estradiol.…”
Section: Discussionsupporting
confidence: 90%
“…This is in accordance with the research of Anita et al in 2019 which stated that there exists "familial aggregation" in familial correlations of obese/overweight state during early days of life whereby daughters are more likely to be inflicted upon by parental indices of adiposity than sons. Consistent with these lines, a positive history in family for obesity cases has been highlighted in the present study to be one of the major diagnostic risk factors for the onset of weight gain, equally suggested by many other studies (Mangla et al, 2019). In obese patients, inflammation of adipose tissue occurs and causes insulin resistance and an increase in aromatase expression (in this case the CYP2C19 gene polymorphism) which converts testosterone to estradiol.…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed factor loadings ranged of satisfied from (54.1%) to (95.6%), while the total Child Feeding satisfied were (98.7%) and the data ranged from(60-125)by mean +SD(97.307±10.705), regarding the perceived responsibility the majority of parental in the satisfied were (90.2%) and the data ranged from (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)by mean +SD(11.441±2.747)(see table3). Birch et al did not find a correlation between perceived responsibility and restriction [31], our findings are consistent with those of a study involving Turkish mothers [30].…”
Section: Discussionmentioning
confidence: 54%
“…[30] This is present in our study of the high percentage of satisfaction our study the perceived parent weight the majority of parental in the satisfied were (95.6%) and the data ranged from (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)by mean +SD(12.090±1.268). while 3erceived child weight the majority of parental in the satisfied were (95.6%) and the data ranged from(4-16)by mean +SD(11.693±1.413), regarding Concern about child weight the majority of parental in the satisfied were (54.1%) and the data ranged from (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)by mean +SD(7.869±3.367) (see Table3), supported our study Saudi mothers reporting their child with a lower weight reported a higher picky eating score. Picky eaters are often underweight; hence, parents may have less concern of overweight.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The obesity outbreak has been estimated by the World Health Organization to surpass even 1 billion of overweight adults in count, 300 millions of which are already clinically obese [1] [2] [3]. Body fat distribution and accumulation in abdominal region confers the highest risk for fatality with varying degrees of obesity [1]; controlled substantially by living trends [4] and familial backdrop [5]; with its stake prognosticated by body's biological age [6]. Abdominal obesity, to be specific, is amongst the most important modifiable risk factors for continual rise in the risk of early onset of several chronic disorders [1].…”
Section: Introductionmentioning
confidence: 99%